Conversion of a Surgical Elbow Arthrodesis to Total Elbow Arthroplasty - Dominik Rog; Lee M. Zuckerman; Barth Riedel (Case Reports in Orthopedics)
Arthrodesis of the elbow joint addresses pain due to intra-articular pathology, but with significant functional limitations. Loss of motion at the elbow is not completely compensated by the wrist and shoulder joints and elbow fusion is thus purely a salvage procedure. Advances in joint arthroplasty have allowed surgeons to address the functional limitations of arthrodesis, but despite these advances the elbow is still one of the joint replacements with higher complication rate. Conversion of a joint fusion to arthroplasty has been reported for the hip, knee, shoulder, and ankle. The takedown of a surgically fused elbow was reported in German literature in 2013. We present the first such case report in the English literature with a 49-year-old male whose status is elbow fusion performed for trauma 31 years prior.